The system of contracts governing the activities of microcredit organizations - Umarov, Khusanboy (Результаты научных исследований в условиях пандемии (COVID-19), 2022)
The article discusses the system of contracts for legal regulation of services provided by microcredit organizations. The articlealso discusses the features of microcredit, microcredit, microleasing, microfactoring and consulting contracts